Naskh dan Mansukh dalam al-Qur’an: Tinjauan Kritis atas Pro dan Kontra - Ratoni (Prodi Ilmu al-Qur'an dan Tafsir, 2025)
This study examines the concept of Nasikh and Mans?kh (abrogation) in the Qur'an, analyzing both supporting and opposing views among scholars. The research focuses on three main aspects: (1) the essential nature of Nasakh and Mans?kh and their distinction from related concepts like Takhshis (specification) and Bada' (divine alteration); (2) the scholarly debate surrounding their existence in the Qur'an, including various theological arguments; and (3) an evaluation of the most substantiated positions on this issue. Employing qualitative methodology through library research and content analysis, the study finds that the majority of Islamic scholars across different eras have affirmed the reality of Nasikh and Mans?kh in the Qur'an. This consensus is not merely based on tradition, but on substantial textual evidence, logical arguments, and clear indicators within Islamic sources. Conversely, the minority view that rejects the concept appears to lack compelling evidence, often relying on strained interpretations that prove counterproductive to their position. The study concludes that the principle of abrogation does not contradict the perfection of divine revelation, but rather reflects divine wisdom in legislative progression. The phenomenon demonstrates Allah's mercy in adapting religious laws according to changing circumstances and human welfare needs. Far from being problematic, Nasikh and Mans?kh represent a sophisticated aspect of Qur'anic legislation that accommodates temporal and contextual considerations while maintaining the eternal truths of Islam. The research highlights how this mechanism ensures the relevance and applicability of Islamic law throughout different historical periods and social conditions.